Design and Implementation of an Enhanced Recovery After Surgery Protocol in Elective Lumbar Spine Fusion by Posterior Approach: A Retrospective, Comparative Study. Issue 12 (15th June 2021) - Garg, Bhavuk; Mehta, Nishank; Bansal, Tungish; Shekhar, Shubhankar; Khanna, Puneet; Baidya, Dalim Kumar
Abstract : Study Design: Retrospective, comparative. Objective: The aim of this study was to design an enhanced recovery after surgery (ERAS) protocol for elective lumbar spine fusion by posterior approach, and to compare the results after ERAS implementation in patients undergoing elective lumbar spine fusion with conventional perioperative care. Summary of Background Data: Despite wide adoption in other surgical disciplines, ERAS has only been recently implemented in spine surgery. The integrated multidisciplinary approach of ERAS aims to reduce surgical stress to achieve better outcomes. Methods: Hospital records of adult patients who underwent one- to three-level elective lumbar spine fusion by posterior approach at a single center were retrospectively studied. An ERAS protocol was designed based on the prevalent hospital practices, local resources and supportive evidence from literature. The ERAS protocol was implemented at our institute in December 2016—dividing patients into pre-ERAS and post-ERAS groups. The outcome measures for comparison were: length of hospital stay (LOS), postoperative complications, 60-day readmission rate, 60-day reoperation rate, and patient-reported outcome measures (visual analogue scale [VAS] and Oswestry Disability Index [ODI] score) at stipulated time intervals. Results: A total of 812 patients were included – 496 in the pre-ERAS group and 316 in the post-ERAS group. There was no significant difference between the two groups in baseline demographic, clinical, and surgery-related variables. Patients in the post-ERAS group had a significantly shorter LOS (2.94 vs. 3.68 days). The rate of postoperative complications (13.5% vs. 11.7%), 60-day readmission (1.8% vs. 2.2%), and 60-day reoperation (1.2% vs. 1.3%) did not differ significantly between the pre-ERAS and post-ERAS groups. The VAS and ODI scores, similar at baseline, were significantly lower in the post-ERAS group (VAS: 49.8 ± 12.0 vs. 44 ± 10.8, ODI: 31.6 ± 14.2 vs. 28 ± 12.8) at 4 weeks after surgery. This difference however was not significant at intermediate-term follow-up (6 months and 12 months). Conclusion: Implementation of an ERAS protocol is feasible for elective lumbar spine fusion, and leads to shorter LOS and improved early pain and functional outcome scores. Level of Evidence: 3 Abstract : An enhanced recovery after surgery (ERAS) protocol was designed and implemented in in adult patients who underwent elective lumbar spine fusion by posterior approach. The implementation of ERAS resulted in shorter hospital stay and improved pain score and functional outcome at early follow-up in this retrospective, comparative study.